(untitled) (Research, Society and Development, 2025)
Given our strong dependence on computers and online resources, data protection has become crucial. Number Theory, especially prime factorization, plays a fundamental role in current cryptographic systems such as RSA, ensuring that information remains confidential and authentic. This study aims to examine how prime factorization is employed in cryptography, addressing factoring methods, the functioning of RSA, its limitations, and the impact of quantum computers. It also addressed the need for encryption resistant to quantum attacks and the integration of different fields such as mathematics, technology, and regulation. The results indicate that mathematics not only supports digital security but also needs to continuously adapt to new technologies and emerging threats. Therefore, research and the development of new security strategies are indispensable.